A Framework for Assessing the Environmental Benefits of Mass Timber Construction. (2017) - Crawford, Robert H.; Cadorel, Xavier
Abstract: The construction industry represents one of the most significant contributors to human-induced environmental damage. Many of the negative consequences on the environment result from the extraction, processing and manufacture of construction materials and components. This includes the depletion of raw material, energy and water resources; loss of habitats; contamination of water and soil; reduced air quality; and climate change. The production of some of the most common construction materials, such as concrete, steel, glass and aluminum are of most critical concern. There is a growing awareness of the need for a greater use of renewable materials that not only reduce resource depletion, but also address the range of other environmental issues. Cellulose-based materials, such as timber and straw are a commonly used renewable alternative. While timber has been used in construction for many centuries, there has been a recent resurgence in the use of timber as a replacement for traditional concrete and steel structures, particularly in response to these pressing environmental imperatives. Mass timber construction (MTC) is seen as a potentially viable alternative for dealing with these issues while at the same time meeting the demands of modern buildings, such as increasing height, speed of construction and fire resistance. Most existing research on MTC has been centered on its structural performance and fire resistance. There is a general lack of understanding of how this form of construction performs from an environmental perspective, which is critical given this is considered as one of its main strengths. This study establishes a framework for assessing the environmental benefits of MTC. The aim is to provide a streamlined approach to enable key building project stakeholders to assess the potential for MTC to provide environmental benefits over traditional construction methods in a particular building project. This can provide useful guidance for decision-making in relation to the use of MTC.